Right ventricular reverse remodelling in Idiopathic Pulmonary Arterial Hypertension diagnosed during pregnancy: Is it possible?. (2017) - Paciocco, Giuseppe; Lombi, Andrea; Vincenzi, Antonella; Pesci, Alberto; Achilli, Felice
Abstract: We present a case of a 36-year-old woman who developed a severe form of Idiopathic Pulmonary Arterial Hypertension (IPAH) during pregnancy and after emergency delivery. The management of IPAH during or after pregnancy is complex. Due to the severity of her IPAH, an upfront triple combination therapy, including i.v. epoprostenol, was started. The rapid institution of this treatment regimen allowed a complete right ventricular reverse remodelling after 1 year of therapy, leading to a down-titration until complete suspension of epoprostenol from the treatment regimen.